Determining the Layout Parameters of the Gas Drainage Roadway: A Study for Sima Coalmine China - Zhiliu Wang; Bo Liu; Yanhui Han; Zhaoyang Li; Yingjie Cao; Fuzhou Qi (Advances in Civil Engineering)
To determine the layout parameters of the gas drainage roadway (GDR) serving for the working face, an analytical calculation method of fracture zone and the modelling experiment were adopted, and the overburden fissure induced by mining and the height of fracture zone were analyzed. For the research on the distribution of fracture zone by analytical calculation method, the multiple factors influencing the failure mode of strata and the height of fracture zone were considered. The #1207 working face in Sima mine was taken as an engineering background, and the layout parameters of GDR were given by analyzing the height of fracture zone. Combining the results obtained by analytical calculation and scale modelling experiment, the suggested height of GDR was 10.7–32.8 m away from the coal seam roof, and the projection distance of GDR in the horizontal was within the range of 0–35 m from the airway. By monitoring the gas drainage effects in different heights away from coal seam roof in #1207 working face and in different horizontal distances away from the ventilation roadway in the #1211 working face, the results showed that the optimal height was 17.5–22 m away from coal roof, and the optimal horizontal distance was 17–21 m away from airway for GDR. The gas drainage effect of GDR indicated that the proposed parameters are scientific and reasonable.